Uwagi do łacińskich inskrypcji z fary poznańskiej - Rosół , Rafał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
The Parish Church in Poznań (the former Jesuit Church) is known to house about 200 Latin inscriptions. The majority of them have not been investigated in detail yet. The paper deals with six different inscriptions that require some comments from the philological or cultural point of view.